The solution to drug resistance of Gram-negative bacteria – Cefiderocol - Kołodziej, Magdalena; Gorczyca, Kamila; Jastrzębska, Ilona; Węgorowski, Paweł; Wieczorek, Michał (Journal of Education, Health and Sport, 2023)
Introduction: A major public health problem is the emergence of anti-gram-negative antimicrobial resistance worldwide. Cefiderocol is a new agent targeting Gram-negative bacteria, including strains with resistance to carbapenems. Aim of the study: Analysis of the efficiency of cefiderocol in the treatment of infections caused by gram-negative bacteria, the drug’s mechanism of action and pharmacokinetics and pharmacodynamics of the drug. Material and Methods: Search of the PubMed database using the following keywords: cefiderocol, resistance, gram negative bacteria. Only full-length articles were taken into consideration. Results: The studies show that cefiderocol is active against Enterobacteriaceae, P. aeruginosa, B. cepacia and A. baumannii and effective in the treatment of pneumonia in both non-ventilated and ventilated patients. Moreover, it has been used in the treatment of sepsis as a rescue therapy. Conclusion: Cefiderocol is an effective treatment for infections caused by gram-negative bacteria. However, more research is needed to learn more about the use of this drug, side effects and resistance mechanisms.